Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Haider S.; Masood M.U.; Rashid M.; Ali T.; Pande C.B.; Alshehri F.; Elkhrachy I. (Elsevier B.V., 2024)
Globally climate and land use change have put stress on the natural water resources which are depleting rapidly. This study's goal is to explore the rainwater harvesting (RWH) potential for Lahore city. Average annual rainfall records were used along with future projections of precipitation by global climate model GCM (MPI-ESM12-HR) under two shared socioeconomic pathways (SSP2 and SSP5) to find the potential of rainwater harvesting. Land use land cover (LULC) maps of past (2010), present (2022) and future time periods (2035 and 2050) and built-up area for Lahore city was calculated in Arc Map using a geometry dialogue box that was estimated to be 1299.86 km2 of land in the year 2050. By the middle of the twenty-first century, rainfall in the Lahore district is predicted to increase by 12% and 16%, from 698.0 mm in the baseline time period (19902015) to 781.7 mm and 809.6 mm, respectively. This increased precipitation over the extent of built-up area could be harvested and utilized for different domestic, industrial, recreational and environment protection purposes. The study also concluded that RWH not only save the Lahore from urban flooding due to rain but also have potential to realize about 39.8% of water deficit of total water demand for Lahore. The daily supply capacity from Ravi River and WASA is 632 million gallon which is equal to only 54% of total water demand. The shortage of 487.2 million gallon per day could be succeed by using rainwater which have potential to realize about 19% of water shortage. In a similar manner, it is indicated based on outcomes of this study that method of RWH is very appropriate for major cities like Lahore in order to address present climate and land use change concerns, particularly in water-stressed nations like Pakistan. 2023 Elsevier B.V.